PERBANDINGAN EFEKTIFITAS CUCI TANGAN TUJUH LANGKAH DENGAN AIR DAN DENGAN SABUN CUCI TANGAN CAIR DALAM MENJAGA KEBERSIHAN TANGAN PADA MAHASISWA/I FAKULTAS KEDOKTERAN UNIVERSITAS JAMBI (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2018)
Background: Hand washing is one indicator of Clean and Healthy Lifestyle. One of the scopes is in a school environment or educational institution. Hand washing with water alone is more common, it is not effective in maintaining health than hand washing with soap. Washing hands with soap causes us to allocate more time while washing hands, but the use of soap is more effective because the fat and dirt on the hands will be released when the hands are rubbed and rubbed with soap. The purpose of this research is to know the comparison of the effectiveness of hand washing seven steps with water and with handwashing soap in order to keep hand hygiene. Methods: This study used analytical method with two groups pretest-posttest experimental design with random sampling technique. The sample in this study was cotton swap on the fingers of students with 90 students. The cotton swab is grown on a nutrient agar medium in a petri dish, and counts the number of colonies after incubation 16-18 hours at the incubator at 37 °C. Data analysis technique using statistik with p value which is considered significant is p <0,1. Result: The effectiveness of handwashing with water and soap use is defined as the sum of germ colonies washing seven-step hands with water group and the sum of germ colonies washing seven-step hands using liquid hand soap group. The results of statistical analysis with Mann Whitney test, significance value P = 0.071. Significance value P <0.1 indicates that there is a difference between the effectiveness of handwashing with water and soap in reducing the number of bacterial colonies. Conclusion: Hand washing seven steps with soap more effective than washing hands seven steps with water only. Keywords: Hand washing seven steps, liquid hand washing soap